Dialogue With Ancestors? Documentation Data From Akie In Tanzania - Legère, Karsten; Heine, Bernd; König, Christa (My University, 2022)
The Akie language (khúúti táa Akiyé ‘language of Akiye people’) is a small Southern Nilotic language spoken in Central Tanzania (Manyara and Tanga Region) by approx. 300 people (among them 90 persons rated as language experts and guardians). Since 2009 this critically endangered language has been studied in a project funded initially by SIDA and since 2012 by the Volkswagen Foundation as part of the DoBeS initiative. The project focus has been on Akie documentation, mainly making audio and video recordings of a wide range of multifaceted speech events. In the recordings, a number of discourse markers (DMs) were identified. Of particular interest is the marker hm the role of which resembles an English sentence adverb like ‘yes’ or ‘no’. Its use is quite limited, being mainly selected by late Lesakat and other elders. Its main function is establishing contact with an imaginary target group called asííswe ‘ancestors’. The latter are said to be always present whenever something happens in the community. Their presence is in particular assumed during rituals such as blessing e.g. beer and weapons or wishing people a safe journey when travelling. Taking the presence of asííswe into account is a custom which is deeply rooted in Akie traditions and belief. Accordingly, the elders invite ancestors (often by name) to have a drink and some food, before they are requested to give way to the guests of the blessing. It is also a sort of appeasement, because ancestors can be harmful if they are not properly respected. In the blessing ceremony, the performing (fe)male elder answers on behalf of the asííswe with mh which is an imaginary confirmation of somebody’s presence, similar to roll calls in English. In the paper, samples of Akie texts and the latter’s English translation illustrate the linguistic component of the ceremony.
Keywords: Akie Language; Tanzania; Ancestors; Documentation Data